Multi-objective single DGPV planning in transmission system using artificial immune systems optimization technique / Sharifah Azwa Shaaya, Ismail Musirin and Shahril Irwan Sulaiman - Shaaya, Sharifah Azwa; Musirin, Ismail; Sulaiman, Shahril Irwan (Universiti Teknologi MARA, 2021)
In this paper, a compensation scheme to impose an acceptable transmission system voltage profile and to minimise its active power loss while keeping a low cost was orchestrated. Loss and voltage of a power system are significant issues as they effect the power system quality of service. The installation of DGs has shown positive impacts to reduce system loss with some sideenhancement on the system voltage. This paper analyses the effect of installing DG to reduce the transmission system loss while at the same time ensuring the system voltage is within allowable operating limit with a DG cost constrained. The Optimal DG sizes and location were determined using Artificial Immune Systems (AIS). IEEE 30-Bus reliability test system was used as the transmission testbed. The results demonstrate that an optimal single real-power DG is able to ensure that the transmission voltage can be sustained within a recommended limit and at the same time reduce the system loss with minimal DG cost, which in turns would be beneficial to the power provider.